Pengembangan Metode PQRST Pada Pembelajaran Drama Berbasis Naskah Pada Peserta Didik Kelas XI MIPA SMA Negeri 1 Ketanggungan - Aas Ariska; Ghufroni Ghufroni; Prasetyo Yuli Kurniawan (Peneliti.net, 2022)
Handbooks are important teaching materials as a complement to modules in learning by using the PQRST method in script-based drama learning. The purpose of this study is to describe the needs, compile drafts, and validate experts. This research uses the research method and development (R&D) is to use the ADDIE development model. The results of this study are a handbook of the PQRST method that meets the needs of students and teachers, as well as a draft handbook of the PQRST method. Based on the results of validation tests by several experts, this handbook is suitable for use in script-based drama learning.